Phospholipase A2-Induced Degradation and Release from Lipid-Containing Polymersomes - Mumtaz Virk, Mudassar (Langmuir : the ACS journal of surfaces and colloids, 2018)
Hybrid vesicles, comprising blends of amphiphilic block copolymers and phospholipids, have attracted significant attention recently because of their unique combination of chemical and physical properties. We report a method to make unilamellar hybrid vesicles with diameters of 100 nm by mixing polybutadiene-block-poly(ethylene oxide) and phosphocholine lipids using a combination of solvent inversion and sonication. We show that homogeneous hybrid vesicles are formed when one component is a minor fraction. At compositions with balanced mass fractions, separate populations of similarly sized pure liposomes and hybrid vesicles are indicated. We investigate the release kinetics of calcein encapsulated in the lumen as hybrid large and giant unilamellar vesicles (LUVs and GUVs) of different compositions are exposed to phospholipase A2 (PLA2). PLA2 hydrolyzes lipids, which leads to dissolution of lipid domains and provides a trigger for the release of calcein as pores are formed. We demonstrate that depending on the polymer mole fraction, block copolymers can either protect or boost the rate of lipid degradation and thereby the release rate from nanoscale hybrid vesicles. Strong indications of lipid phase separation into nanoscale domains in LUVs are observed. Most importantly, hybrid GUV with lipids in the fluid phase release calcein slowly as lipids in the liquid-disordered phase do not phase-separate, but they show the fastest release of all blends as LUVs. This indicates phase separation on the nanoscale in contrast to on the microscale, but it also indicates retained high mobility of lipids between the nanoscale domains, which is absent for lipids in the gel phase. Our results demonstrate several ways in which nanoscale hybrid vesicles can and should be optimized for PLA2-triggered release of water-soluble compounds